The adoption of communication and information technologies and the local development - Tiago, Maria Teresa Borges; Couto, João Pedro; Natário, Maria Manuela dos Santos; Braga, Ascensão Maria Martins (Journal of Business Economics and Management, 2007)
This paper examines the imbalances in the availability and usage of communication and information technology infrastructure. These imbalances could be broadly attributed to differences in funding, management and technical expertise, exposure and awareness of available technologies, training, and other infrastructures like R&D institutions. In our sample, the imbalances could be broadly attributed not only to differences in such factors as industry, dimension, management education, but also to lack of cooperation, workers mobility and reduced markets which are common factors in disfavoured regions. First Published Online: 14 Oct 2010